Some Improved Classes of Estimators in Stratified Sampling Using Bivariate Auxiliary Information - Shashi Bhushan; Anoop Kumar; Ronald Onyango; Saurabh Singh (Journal of Probability and Statistics)
This manuscript considers some improved combined and separate classes of estimators of population mean using bivariate auxiliary information under stratified simple random sampling. The expressions of bias and mean square error of the proposed classes of estimators are determined to the first order of approximation. It is exhibited that under some particular conditions, the proposed classes of estimators dominate the existing prominent estimators. The theoretical findings are supported by a simulation study performed over a hypothetically generated population.